ANALYSIS OF WORK MOTIVATION IN IMPROVING EMPLOYEE PERFORMANCE AT THE BUMI JAYA OIL PALM PLANTATION VILLAGE UNIT COOPERATIVE, TELUK GELAM DISTRICT, OKI REGENCY - Supriadi, Supriadi; Prima, Aldi; Marjohan (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2022)
This study entitled "Analysis of work motivation in improving employee performance at the Bumi Jaya Oil Palm Plantation Village Unit Cooperative, Teluk Gelam District, OKI Regency", aims (1) to determine and analyze work motivation in improving employee performance at the Village Plantation Unit Cooperative. Palm Oil (KPKS) Bumi Jaya Teluk Gelam District OKI Regency (2) To find out the efforts made by the Bumi Jaya Oil Palm Plantation Village Unit Cooperative (KPKS) in Teluk Gelam District OKI Regency in improving employee performance through work motivation. The type of research used is qualitative research methods. Qualitative research method is a research procedure that produces descriptive data in the form of written or spoken words from people and observable behavior. The data required include secondary data and primary data obtained in various ways, including: documentation, interviews, observations. The results of employee performance motivation analysis are still low, seen from the indicators of work motivation, namely 1) remuneration, 2) working conditions, 3) work facilities, 4) work performance, 5) recognition from superiors, 6) the work itself. While the performance indicators are 1) work quality, 2) work quality, 3) work constraints, 5) work attitude. The leadership's efforts to improve employee performance through motivation include establishing discipline, creating a conducive climate, providing incentives, and compensation. The type of motivation used to improve employee performance is in the form of salaries, bonuses, work facilities, praise, rewards, and punishments. The conclusion from the results of the study is that the implementation of work motivation carried out by the Bumi Jaya Oil Palm Plantation Village Unit Cooperative, Teluk Gelam District, OKI Regency is considered not good, there are still obstacles faced in improving employee performance, Suggestions for leaders to improve the quality of human resources, create a good cooperative relationship, provide sanctions to employees who violate the rules.